Magneto-transport Spectroscopy of the First and Second Two-dimensional Subbands in Al(0.25)Ga(0.75)N/GaN Quantum Point Contacts - Lu, Fangchao (Sci Rep, 2017)
Magnetic transport spectroscopy is investigated in quantum point contacts (QPCs) fabricated in Al(0.25)Ga(0.75)N/GaN heterostructures. The magnetic field perpendicular to the two-dimensional electron gas (2DEG) is shown to depopulate the quasi-one-dimensional energy levels in the first two-dimensional (2D) subband faster than those in the second one. In GaN based heterostructures, the energy levels in the second 2D subband is generally concealed in the fast course of depletion and hence rarely detected. The perpendicular magnetic field facilitates the observation of the second 2D subband, and provides a method to study the properties of these energy levels. A careful analysis on the rate of the magnetic depletion with respect to the level index and confinement is carried out, from which the profile of the lateral confinement in GaN based QPCs is found to be triangular. The stability diagram at [Image: see text]T shows the energy separation between the first and second 2D subband to be in the range of 32 to 42 meV.